Medical image computing and computer-assisted intervention -- MICCAI 2016. 19th International Conference, Athens, Greece, October 17-21, 2016, Proceedings /: 19th International Conference, Athens, Greece, October 17-21, 2016, Proceedings. Part I : (2016) - Unknown
No abstract available